Analisis Waste Defect Product pada Osha Snack menggunakan Statistical Process Control - Prameswari, Halissa Dwinta; Adinda Norma Cahya Ningrum; Putri Agni Cova; Gracesella Ananda; Alivia Putri Ramadhani; Fany Apriliani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Osha Snack UMKM faces issues related to product defects, which are suspected to arise due to a lack of quality control in the production process. This study aims to identify the causes of product defects, provide improvement suggestions, and determine effective ways to control product quality. Data were collected through interviews with relevant parties and field surveys to gather information on production volume, product defects, and production activities. The data were processed by organizing it into check sheets, performing regression calculations, and analyzing it using scatter diagrams and fishbone analysis. The Statistical Process Control (SPC) method was applied to analyze, control, and improve the production process. The results show a significant relationship between production volume and the number of defective products, with the regression equation Y = 0.0764X and a coefficient of determination R² = 0.9625. The most common type of defect is broken snacks before packaging. In addition, waste products also come from product returns by buyers, which leads to raw material waste and hinders the achievement of production targets. The analysis results suggest that the UMKM should implement quality control measures in the form of process improvements, enhancement of work skills, proper machine maintenance, implementation of SOPs, and improvement of working conditions.